Xanthate-modified alginates for the removal of Pb(II) and Ni(II) from aqueous solutions: A brief analysis of alginate xanthation - Córdova B.M. (2021)
Mining is the most common activity that introduces heavy metal ions into aquatic ecosystems, especially in low income-developing nations where governments are implementing stricter regulations for industrial wastewater. In this context, this work is focused on the application of xanthate-modified alginates for the removal of Pb(II) and Ni(II) from aqueous solutions. In order to confirm the presence of xanthate groups alongside alginate chains, characterization by second-derivative FT-IR was carried out and significance evidence attributed to xanthate groups was found at around 1062–1079 cm−1, 829–845 cm−1 and 620–602 cm−1. In addition to this, thermogravimetric analysis and differential scanning calorimetry were employed to explore thermal properties of modified alginates. According to these results, enthalpy changes (∆H) characteristic of dehydration and collapse of biopolymeric structure were estimated as +11.41 J/g and −6.83 J/g, respectively. Furthermore, the presence of S element was confirmed by EDS mapping technique, whereas FESEM image showed a cracked and homogeneous surface distribution. On the other hand, the effect of important parameters such as pH, dosage, initial concentration as well as Langmuir and Freundlich isotherm were deeply discussed. Finally, rheological measurements were performed aiming to investigate the gel-like viscoelastic features associated to nickel xanthate compound. © 2021 Elsevier B.V.